A Sustainability 3D Framework of the 20 Regions of Italy and Comparison With World Countries - Pulselli, Federico M.; Sani, Alessandro; Goffetti, Giulia; Coscieme, Luca; Bastianoni, Simone (Frontiers in Energy Research, 2019)
An Input-State-Output (I-S-O) framework has been recently introduced to investigate the multidimensional aspects of sustainability (namely environmental, social and economic ones) of economic systems through a thermodynamically and logically ordered scheme. This approach provides an overall view of sustainability (the three dimensions together) facilitating the convergence of information from sets of indicators without aggregating results into single numbers and, consequently, losing information. In this paper we present the application of the I-S-O framework for the 20 regions of Italy. The emergy flow, the Gini Index of income distribution, and the regional Gross Domestic Product are used as systemic indicators for input, state, and output of the systems, respectively. We observe diversity among regions in the light of very different values of the three indicators. The per capita use of resources in the North of Italy is generally 2 to 4 times larger than in the South (excluding Puglia and Sardegna); the regional GDP per capita in the North doubles that of the Southern regions. The distribution of income, that is slightly better in two regions of the north (Trentino AA and Friuli VG), some of Center Italy, and Puglia in the South, only partially reflects that North-South discrepancy. Using the same measures, the 20 Regions are included in a global overview recently produced for 99 world countries. Regional values cover a wide range of countries; nevertheless, our values tend to be more similar to those of developed countries. Based on indicator values, Regions are also categorized, which enables interpretation of this overview at both sub-national and supra-national level.